Evaluasi Praktik Ekowisata di Kampung Tradisional Bena, Desa Tiwuriwu, Kabupaten Ngada, Nusa Tenggara Timur - Balduinus Bonaventura Bata; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2022)
Bena traditional village is a tourist village located in Tiwuriwu Village, Ngada Regency, NTTProvince. This tourist village develops ecotourism as the basis for its tourism products. Ecotourismpractices in Bena Village that have been running have a significant impact on environmentalsustainability, utilizing socio-cultural economics for the local community. This study aims to evaluate thefeasibility of ecotourism practices in Bena village by using ecotourism principles as a parameter todetermine the feasibility of ecotourism. Qualitative method is used as a tool to analyze this research with aqualitative descriptive approach. The data were searched by using interview, documentation andobservation methods. The results showed that several ecotourism practices in Bena village were inaccordance with the principles of ecotourism. Practices that do not meet the principles of ecotourismrequire a strategic model that is able to meet these deficiencies.Keywords : Ecotourism, Principle, Practice